Study on the quality characteristics of jujube slices under different pretreatment and drying methods - Zhengdong Wan; Zhuofan Ji; Dandan Zhao; Yamei Liu; Zhentao Zhang; Jianxiong Hao (Ultrasonics Sonochemistry)
This study investigates the effects of different pretreatment methods, cold plasma (CP) and ultrasound (US), as well as different drying techniques, including vacuum freeze-drying (FD), hot air drying (HAD), and microwave coupled with pulsed vacuum drying (MPVD), on the quality characteristics of winter jujube slices. The physical, chemical, and functional properties were analyzed, encompassing farinograph attributes, particle size, cation exchange capacity, total phenolic and flavonoid content, and flavor compounds were analyzed. In terms of physical properties, jujube slices subjected to MPVD demonstrate superior water-holding capacity at 2.93 g/g and enhanced fluidity, with a sliding angle of 34.98° and an angle of repose of 43.47°, compared to FD jujube slices. Additionally, it exhibits a rehydration capacity of 2.98 g/g and a bulk density of 0.49 g/mL. Regarding chemical composition, the cation exchange capacity of US-FD jujube slices is measured at 0.64 mmol/g, while the total phenolic content reaches 11.97 mg/g, and the flavonoid content in CP-MPVD jujube slices is 5.21 mg/g. Notably, the cation exchange capacity of MPVD jujube slices pretreated by CP and US is 0.46 and 0.55 mmol/g, respectively. Concerning volatile compounds and flavor, FD slices retain higher concentrations of aldehydes (11.39 %) and alkenes (16.88 %), whereas MPVD slices contain 21.20 % alkanes. HAD slices contain the highest aromatic hydrocarbon content at 34.97 %. In summary, the optimized combination of CP and MPVD can enhance the drying efficiency of jujube slices, increase the flavonoid content in jujube slices, and improve their quality characteristics.